Analysis of the diversity of the glycoside hydrolase family 130 in mammal gut microbiomes reveals a novel mannoside-phosphorylase function. Issue 10 (15th October 2020) - Li, Ao; Laville, Elisabeth; Tarquis, Laurence; Lombard, Vincent; Ropartz, David; Terrapon, Nicolas; Henrissat, Bernard; Guieysse, David; Esque, Jeremy; Durand, Julien; Morgavi, Diego P.; Potocki-Veronese, Gabrielle
Abstract : Mannoside phosphorylases are involved in the intracellular metabolization of mannooligosaccharides, and are also useful enzymes for the in vitro synthesis of oligosaccharides. They are found in glycoside hydrolase family GH130. Here we report on an analysis of 6308 GH130 sequences, including 4714 from the human, bovine, porcine and murine microbiomes. Using sequence similarity networks, we divided the diversity of sequences into 15 mostly isofunctional meta-nodes; of these, 9 contained no experimentally characterized member. By examining the multiple sequence alignments in each meta-node, we predicted the determinants of the phosphorolytic mechanism and linkage specificity. We thus hypothesized that eight uncharacterized meta-nodes would be phosphorylases. These sequences are characterized by the absence of signal peptides and of the catalytic base. Those sequences with the conserved E/K, E/R and Y/R pairs of residues involved in substrate binding would target β-1, 2-, β-1, 3- and β-1, 4-linked mannosyl residues, respectively. These predictions were tested by characterizing members of three of the uncharacterized meta-nodes from gut bacteria. We discovered the first known β-1, 4-mannosyl-glucuronic acid phosphorylase, which targets a motif of the Shigella lipopolysaccharide O-antigen. This work uncovers a reliable strategy for the discovery of novel mannoside-phosphorylases, reveals possible interactions between gut bacteria, and identifies a biotechnological tool for the synthesis of antigenic oligosaccharides.